1981
DOI: 10.1128/iai.32.2.583-591.1981
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Streptococcus mutans and Streptococcus sanguis to salivary components bound to glass

Abstract: Adherence of radiolabeled Streptococcus mutans and Streptococcus sanguis to saliva-treated glass surfaces was studied under conditions which minimized bacteria-glass interactions. Treatment of glass with an alkylsilane solution decreased nonspecific bacterial adherence and enhanced adsorption of radiolabeled salivary components to these surfaces. Addition of Triton X-100 to the bacterial suspensions also reduced nonspecific adherence to siliconized glass, but did not affect adherence to salivary components att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…A recent study also reported a positive correlation between the total protein and glycoprotein contents in saliva and saliva-promoted S. mutans adhesion to hydroxyapatite (Shimotoyodome et al, 2007). A number of salivary components, when adsorbed to oral surfaces, were reported to mediate molecular interactions with oral bacteria, including mucins (Stinson et al, 1982), a-amylase (Scannapieco et al, 1993(Scannapieco et al, , 1995, fibronectin (Dawson & Ellen, 1990) and proline-rich proteins (Gibbons & Hay, 1989;Russell & Mansson-Rahemtulla, 1989). Therefore, this pellicle-mediated bacterial adhesion could provide the basis for the robust formation of dental plaque populated with sufficient proportions of cariogens to increase the risk of dental caries.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study also reported a positive correlation between the total protein and glycoprotein contents in saliva and saliva-promoted S. mutans adhesion to hydroxyapatite (Shimotoyodome et al, 2007). A number of salivary components, when adsorbed to oral surfaces, were reported to mediate molecular interactions with oral bacteria, including mucins (Stinson et al, 1982), a-amylase (Scannapieco et al, 1993(Scannapieco et al, , 1995, fibronectin (Dawson & Ellen, 1990) and proline-rich proteins (Gibbons & Hay, 1989;Russell & Mansson-Rahemtulla, 1989). Therefore, this pellicle-mediated bacterial adhesion could provide the basis for the robust formation of dental plaque populated with sufficient proportions of cariogens to increase the risk of dental caries.…”
Section: Discussionmentioning
confidence: 94%
“…A variety of ardficial and natural hard surfaces have been used for in vilro adherence studies, including slabs of bovine enamel (24), glass tubes (22), whale dentine (23), discs of compressed hydroxyapadte (4), saliva-treated glass (31) and Mylar strips (34). The most popular method to date appears to be the adherence assay described by Clark and co-workers in 1978 (3) which uses hydroxyapadte beads as a convenient, well-defined synthedc substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the various cells were harvested by centrifugation (2200 rpm, 19°C, 5 min; Hettich Rotixa P, Tuttlingen, G), washed twice with PBS and re‐suspended in the same buffer. Cell suspensions were subjected to low intensity ultrasonic energy to disperse streptococcal chains (Bandelin Sonorex Super RK 510 H, Bandelin electronic GmbH, Berlin, G),15 and the optical density of the suspensions was adjusted to 0.3 at 550 nm with a spectrophotometer (Genesys 10S; Thermo Spectronic, Rochester, NY), which corresponds to a microbial concentration of 3.65 × 10 8 microorganisms/mL 16…”
Section: Methodsmentioning
confidence: 99%